Relación entre la internacionalización y la innovación en las empresas exportadoras del Área Metropolitana de Bucaramanga - Fernández Pinto, Henry (Editorial Uniagustiniana, 2020)
The project that gave rise to this chapter was aimed at identifying characteristics of innovative processes in the exporting companies of Bucaramanga Metropolitan Area (bma), as well as their internationalization processes. It should be noted that the study variables were selected according to the Oslo Manual. Thus, innovation was analyzed from different modalities: process, product, marketing, and organization. This research was framed within a descriptive quantitative cross-sectional approach over a period of ten years. A sample of 70 exporting manufacturing companies from the bma was selected. As a result, despite innovation was evidenced in all modalities, a decreasing trend was also evident during the study period (2006- 2015). These innovations are, however, only local and within the company and they do not impact internationalization processes since there are no significant increases in exports. It can be added that there are no changes in the low diversification of markets or in the concentration of exports to natural or psychologically close markets.